The Influence of Achievement Motivation on the Academic Achievement of Fashion Students at SMK Negeri 1 Sindang - Dian Zahra Nuraeni; Nurlaeliyah (Journal Of Psychology, Counseling And Education, 2026)
This study aims to determine the level of achievement motivation and academic achievement of students majoring in Fashion at SMKN 1 Sindang. And to analyze the influence between achievement motivation and academic achievement in students majoring in Fashion at SMKN 1 Sindang. This study uses a quantitative approach with a correlation type. Data analysis was carried out using the Pearson Product Moment correlation technique, with the help of the SPSS v.23 program. The study population included 60 students of grades X and XI majoring in Fashion at SMKN 1 Sindang who had a ranking of 1-10. The sampling technique used was total sampling. The results showed that all respondents, 60 students (100%), had achievement motivation in the high category, with none in the medium or low category. In the aspect of academic achievement, as many as 43 students (71.6%) were in the high category, and 17 students (28.3%) were in the medium category, with none in the low category. Pearson Product Moment correlation analysis produced a correlation value (r) of 0.402. Because the calculated r value (0.402) is greater than the table r (0.254) at the 5% significance level, H0 is rejected and Ha is accepted. Thus, there is a significant influence between achievement motivation and academic achievement of Fashion students at SMKN 1 Sindang, with the level of influence being in the moderate category.